2012
DOI: 10.4088/jcp.11m07117
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Sertraline Add-On to Brief Dynamic Psychotherapy for the Treatment of Postpartum Depression

Abstract: clinicaltrials.gov Identifier: NCT01028482.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
1
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(73 citation statements)
references
References 36 publications
2
64
1
5
Order By: Relevance
“…Sertraline in combination with brief dynamic psychotherapy was not better than placebo combined with psychotherapy in causing significant remission in therapeutic randomized controlled trial (Bloch et al 2012).Fluoxetine along with counselling was found to be effective in reducing depression levels when compared with placebo (Appleby et al 1997). Nevertheless, patients receiving 6 sessions of counselling improved most in the study.…”
Section: Selective Serotonin Reuptake Inhibitors (Ssri):-mentioning
confidence: 80%
“…Sertraline in combination with brief dynamic psychotherapy was not better than placebo combined with psychotherapy in causing significant remission in therapeutic randomized controlled trial (Bloch et al 2012).Fluoxetine along with counselling was found to be effective in reducing depression levels when compared with placebo (Appleby et al 1997). Nevertheless, patients receiving 6 sessions of counselling improved most in the study.…”
Section: Selective Serotonin Reuptake Inhibitors (Ssri):-mentioning
confidence: 80%
“…160 The main analysis of all patients provided evidence of no statistically significant difference between add-on sertraline (70%) and placebo (55%) in response rates (>50% reduction in either the MADRS or EPDS scores). The post-hoc analysis of the high depression severity subgroup also found no statistically significant difference in response rate (t=1.05; P=0.31).…”
Section: Severity Of Symptomsmentioning
confidence: 90%
“…We found three small medium risk of bias RCTs 156,160,166 and one small, high risk of bias observational study 73 that compared combining pharmacologic treatments with nonpharmacological treatments and comparing them with nonpharmacological treatments alone. All of the studies focused on the postpartum period only and reported on depression symptoms.…”
Section: Maternal Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…The treatment had very good effect (100% of participants had recovered from depression at follow-up), but there was no differences to the comparison treatment (family therapy, in where 81% no longer were depressed). Using the same manual, Bloch et al (2012) found no differences between dynamic therapy + antidepressants compared to dynamic therapy + placebo in a sample of participants with postpartum depression. However, within-group effects were very large on the primary outcome measure of depression (d = 3.78 and d = 2.56 for dynamic therapy plus antidepressants and placebo, respectively).…”
Section: Experiential Dynamic Therapymentioning
confidence: 90%